2022
DOI: 10.1038/s41598-022-19812-2
|View full text |Cite
|
Sign up to set email alerts
|

Plastomes of limestone karst gesneriad genera Petrocodon and Primulina, and the comparative plastid phylogenomics of Gesneriaceae

Abstract: Petrocodon and Primulina are two characteristic genera of Gesneriaceae that exhibit remarkable species and floral diversity, and high endemism across the Sino-Vietnamese Limestone Karsts. To better understand the evolution of limestone gesneriad plastomes, we report nine complete plastomes of seven Primulina and two Petrocodon which have never been assembled before. The newly generated plastomes range from 152,323 to 153,786 bp in size and display a typical quadripartite structure. To further explore the plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…For example, both Roalson and Roberts (2016) and Li et al. (2022) indicated that Hemiboea was close to Lysionotus with weak supporting values, while Hsieh et al. (2022) supported that Oreocharis was a sister group of Hemiboea based on plastomes with one IR excluded.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both Roalson and Roberts (2016) and Li et al. (2022) indicated that Hemiboea was close to Lysionotus with weak supporting values, while Hsieh et al. (2022) supported that Oreocharis was a sister group of Hemiboea based on plastomes with one IR excluded.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous phylogenetic studies of Didymocarpinae using ITS and trnL-F sequences, relationships within the ‘core’ Didymocarpinae remained poorly resolved [ 75 , 77 , 79 , 86 , 87 , 90 ]. The employment of genomic data such as whole plastome sequences [ 96 ] and target capture [ 101 ] will be essential to clarify and understand this apparent radiation of Asian gesneriad clade.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the most updated classification of Gesneriaceae, Primulina and Deinostigma are both placed in subtribe Didymocarpinae, tribe Trichosporeae, subfamily Didymocarpoideae [ 63 , 77 , 96 , 101 ]. To maximize taxon sampling while exploiting DNA sequences available in the GenBank, we sequenced the internal transcribed spacer (ITS) of the nuclear ribosomal DNA (including the 5.8S gene) and the plastid trnL-trnF intergenic spacer ( trnL-F ), which have been the most widely used molecular markers in reconstructing phylogenetic relationships of Asian Gesneriaceae and delimitating new gesneriad genera [ 74 76 , 86 – 88 , 90 , 102 , 103 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations